Effect of energy consumption, foreign direct investment, and economic growth on greenhouse gas emissions in OPEC member states: evidence from panel data analysis - Gibba, Alieu; Jammeh, Lamin; Jallow, Mamadou Alieu (Frontiers in Environmental Economics, 2024)
Our paper explores the impact of energy consumption, foreign direct investment, and economic expansion on greenhouse gas emissions in OPEC member states. A panel data of 12 out of 13 OPEC nations over the period 1983 to 2022 obtained from the World Development Indicators is used. The autoregressive distributed lag simulation was adopted to determine the correlation among the series. Our estimations unveil that economic growth in the member states contributes 7.47 per cent to greenhouse gas emissions for every 1 percent increase, trade flow tends to reduce greenhouse gas emissions by 0.37 per cent for every 1 percent rise. Though the impact of foreign direct investment on greenhouse gas emissions in the OPEC member states is negative, it is statistically insignificant. The positive association between energy consumption and greenhouse gas emissions emphasizes the need for OPEC countries to move to cleaner energy sources in order to reduce environmental damage. A proactive approach to investing in clean technology is critical for governments and companies in OPEC countries. This includes supporting research and development of renewable energy sources, encouraging the adoption of environmentally-safe practices in industry and fostering innovation to promote sustainable development. Strict environmental standards for industries that contribute significantly to greenhouse gas emissions should be adopted and enforced. This includes: Setting caps on emissions, advocating for cleaner production processes, and imposing penalties for non-compliance with environmental regulations. Sustainable practices should be encouraged through tax incentives, subsidies, and other financial mechanisms designed to incentivized companies to adopt environmentally friendly processes. The implications of these findings for policymakers and future studies are discussed.